2014
DOI: 10.1007/s10815-014-0387-9
|View full text |Cite
|
Sign up to set email alerts
|

Ongoing and cumulative pregnancy rate after cleavage-stage versus blastocyst-stage embryo transfer using vitrification for cryopreservation: Impact of age on the results

Abstract: Purpose To determine if blastocyst transfer increases the ongoing and cumulative pregnancy rates, compared with day 3 embryo transfer, in women of all ages when at least 4 zygotes are obtained. Methods Prospective study including patients undergoing a first IVF/ICSI treatment and assigned to cleavage stage (n= 46) or blastocyst (n=58) embryo transfer. Supernumerary embryos were vitrified and patients failing to achieve an ongoing pregnancy after fresh embryo transfer would go through cryopreserved cycles. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 17 publications
3
57
0
1
Order By: Relevance
“…The following subgroup analyses were performed for ongoing pregnancy/live birth: (1) number of embryos transferred (1; 2; > 2 allowed); (2) 38 Coskun (2000) 39 Emiliani (2003) 40 Fernández-Shaw (2015) 49 Hreinsson (2004) 41 Kolibianakis (2004) 43 Papanikolaou (2005) 46 Papanikolaou (2006) 45 Rienzi (2002) 47 Van der Auwera (2002) …”
Section: Other Analysesmentioning
confidence: 99%
See 4 more Smart Citations
“…The following subgroup analyses were performed for ongoing pregnancy/live birth: (1) number of embryos transferred (1; 2; > 2 allowed); (2) 38 Coskun (2000) 39 Emiliani (2003) 40 Fernández-Shaw (2015) 49 Hreinsson (2004) 41 Kolibianakis (2004) 43 Papanikolaou (2005) 46 Papanikolaou (2006) 45 Rienzi (2002) 47 Van der Auwera (2002) …”
Section: Other Analysesmentioning
confidence: 99%
“…Bungum (2003) 38 Coskun (2000) 39 Emiliani (2003) 40 Fernández-Shaw (2015) 49 Hreinsson (2004) 41 Kolibianakis (2004) 43 Montag (2006) 44 Kaur (2014) 42 Papanikolaou (2005) 46 Papanikolaou (2006) 45 Rienzi (2002) 47 Van der Auwera (2002) (low; atmospheric; unclear), (3) woman's age (mean age ≤ 33 years; unselected); (4) number and quality of available embryos at inclusion (at least four zygotes (day 1); at least three good-quality day 2 or 3 embryos; other studies). One additional subgroup analysis was performed stratifying studies that reported only ongoing pregnancy and those that reported live birth.…”
Section: Study or Subgroupmentioning
confidence: 99%
See 3 more Smart Citations